Enzymatic biosynthesis of novel bavachin glucosides via Bacillus UDP-glycosyltransferase. (February 2018) - Dai, Yiqun; Zhang, Songsong; Liu, Da-Chuan; Li, Hong-Mei; Ma, Tao; Huo, Qiang; Wu, Cheng-Zhu
Graphical abstract: Highlights: Three novel glycosylated bavachin derivatives have been synthesized by in vitro enzyme reaction. Compounds 1–3 displayed better water-solubility than bavachin. Compounds 1–3 were relatively stable under high temperature and different pH conditions. Abstract: A UDP-glycosyltransferase (YjiC) from Bacillus licheniformis was exploited for the glycosylation of bavachin. The in vitro glycosylation reaction generated three novel bavachin glucosides, which were structurally characterized as bavachin-4′- O - β -d -glucopyranoside (1 ), bavachin-7- O - β -d -glucopyranoside (2 ), and bavachin-4′, 7-di- O - β -d -glucopyranoside (3 ) based on spectroscopic techniques. To enhance product yield, the reaction time, buffer pH, and UDP-glucose concentration were optimized. The water-solubility of compounds1, 2, and3 was approximately 5.18, 56.22, and 84.17 times higher than that of bavachin, respectively. In addition, compounds1 -3 displayed the highest stability at pH 8.8 and were stable up to 70 °C for 30 min. Furthermore, the biological activities of bavachin and compounds1 -3 were assayed. Bavachin showed moderate cytotoxicity against four human cancer cell lines while the three glycosylation products displayed weak activity. The results demonstrate that the UDP-glycosyltransferase (YjiC) has the capacity to synthesis bavachin glucosides and that glycosylation of bavachin enhances its water-solubility and stability.